Cerebral hypoperfusion secondary to radiation arteritis presenting with recurrent syncope. (23rd June 2014) - Bashar, Khalid; McHugh, Seamus; Burke, Paul; Kavanagh, Eamon
Abstract : Radiation arteritis can lead to significant extracranial carotid artery stenosis, affecting the circle of Willis. Cerebral hypoperfusion due to arterial insufficiency is often considered as a differential diagnosis in cases of syncope but rarely proven. We present a case of a 61-year-old man with repeated episodes of syncope-negative cardiac investigations. He had a history of cervical radiation therapy for tonsillar squamous cell carcinoma 15 years previously. Carotid duplex revealed bilateral carotid occlusive disease. MR angiography showed severe multilevel extracranial carotid stenosis bilaterally with occluded left vertebral artery. A diagnosis of cerebral hypoperfusion was performed following single-photon emission CT scan. The patient underwent a left subclavian to carotid bypass, which alleviated his symptoms.